Impact of injury-related mortality on life expectancy in Zhejiang, China based on death and population surveillance data - Fang-Rong Fei; Jie-Ming Zhong; Min Yu; Wei-Wei Gong; Meng Wang; Jin Pan; Hai-bin Wu; Ru-Ying Hu (BMC, 2017)
Abstract Background Life expectancy is a statistical measure of the average time an organism is expected to live. The purpose of this study was to evaluate the impact of injury-related mortality on life expectancy in Zhejiang Province. Methods Our study used standard life tables to calculate life expectancy and cause-removed life expectancy based on mortality data from the Zhejiang Chronic Disease Surveillance System. Results Life expectancy of residents in Zhejiang was 77.83 years in 2013, with females having a higher life expectancy than males. The decrease in life expectancy caused by injury-related deaths was 1.19 years, the effect of which was reduced for females and urban residents compared with males and rural residents. The greatest impact on life expectancy was road traffic injuries (RTIs), (0.29 years lost overall, 0.36 for men vs. 0.21 for women and 0.26 for urban residents vs. 0.31 for rural residents). The main causes were falls (0.29 years lost overall, 0.30 for men vs. 0.28 for women and 0.28 for urban residents vs. 0.30 for rural residents), followed by drowning (0.15 years lost), suicide (0.11 years lost), and poisoning (0.04 years). For children less than 5 years old and elders aged over 65, drowning had a greater impact than falls. Conclusions Our findings indicate that injury deaths had a major impact on life expectancy in Zhejiang. More attention should be paid to road traffic injury, and preventive action should be taken to reduce injury-related deaths to increase life expectancy, especially in children under five years of age and the elders over 65 years of age.